Idiopathic scoliosis: general characteristics and analysis of etiological theories (literature review) - E. L. Strokova (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Idiopathic scoliosis is a severe pathology of the musculoskeletal system that affects children and adolescents all over the world. The disease occurs in approximately 0.2-0.6% of the general population, and is the largest subgroup of spinal curvature in humans (70-90% of all known scoliosis cases). In idiopathic scoliosis, a threedimensional deformation of the vertebral column is formed, leading to the formation of a rib hump, curvature of the ribs and chest, asymmetry of the pelvis and impaired development of internal organs. The main feature of the disease is the spontaneous development of deformity during the growth of the child and the tendency to progress. Scoliosis is not only an orthopedic disease, but also a ignificant cosmetic, and, consequently, a psychological and social problem. The standard of treatment for scoliotic disease remains unchanged for a long time: observation, corset treatment and surgical correction. The prognosis for the development of pathology varies depending on the degree of deformation. The corset-therapy, hospitalization, surgery and treatment of chronic back pain have a negative impact on the psychoemotional state of children and adolescents. Despite significant advances in the methods of diagnosis of deformity, improvement of surgical treatment methods and in the study of pathogenesis, the etiological factor of pathology is still unknown. The search for the causes of idiopathic scoliosis covers almost all aspects of its possible origin: genetic, environmental, hormonal, metabolic, biochemical, neurological, and others. In recent decades, relevant theories of the development of scoliosis have been formulated, but none of the theories reveals the essence of the pathological process and has no clear justification. The greatest number of supporters is the genetic theory: genetic factors play a key role in the occurrence and development of idiopathic scoliosis. Understanding the underlying factors of the disease will enable prevention, early diagnosis, and identification of the risk groups of the patients in question.